Power Networks in the House of the Queen of Portugal (14th-15th Centuries) (Edad Media. Revista de Historia, 2026)
This article focuses over the noble population of the the House of the Queen of Portugal from the late fourteenth to the early fifteenth century, with the aim of examining its strategies and power networks. The study is based on three lineages – Afonso, Pereira, Coutinho/Moura – and the perspective is diachronic and comparatist, situating itself historiographically in the fields of Political History, Gender History and History of Nobility. The main sources are the chancelleries of King Ferdinand I, Master of Avis/ João I and King Duarte, and the chronicles of Fernão Lopes. The study emphasises the social ascension of these lineages in the royal court, over generations and reigns, through blood, marriage and royal service.
Keywords: Portugal; Queen's House; King's House; lineages; centuries XIV-XV